2022
DOI: 10.7759/cureus.28894
|View full text |Cite
|
Sign up to set email alerts
|

Predictors That Identify Complications Such As Anastomotic Leak in Colorectal Surgery: A Systematic Review

Abstract: Leakage of the anastomotic site is considered to be one of the most serious complications after colon and rectal surgery. It is associated with increased mortality, morbidity, and longer hospital stays. This systematic review examines the need for blood markers such as C-reactive protein (CRP), procalcitonin (PCT), albumin, and various other molecular markers that assist in their propensity to diagnose anastomotic leakage (AL) early after surgery. Utilizing PubMed and Google Scholar as resources and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Early detection of leakage at the anastomotic site helps in the early detection, treatment, and prevention of post-operative complications, sepsis, and mortality. There are different strategies for identifying AL using different markers, including C-reactive protein (CRP), white cell count (WCC), and procalcitonin (PCT) [19][20][21] . CRP is being studied as a specific early protein marker for postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Early detection of leakage at the anastomotic site helps in the early detection, treatment, and prevention of post-operative complications, sepsis, and mortality. There are different strategies for identifying AL using different markers, including C-reactive protein (CRP), white cell count (WCC), and procalcitonin (PCT) [19][20][21] . CRP is being studied as a specific early protein marker for postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…The tendency for CRP usually increases 48 h after surgery. A steady trend showing increased inflammatory markers, such as CRP, WCC, and PCT would suggest looking out for an AL with the clinical features [19][20][21] . Their levels between post-operative days 3 and 7 are carefully taken into consideration as they could be the predictor of the leak 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review of biomarkers for the detection of AL after colorectal surgery showed that CRP and procalcitonin (common inflammatory markers) could be reliable markers for the prediction of AL [ 14 ]. Other candidate markers, including oxidative stress markers and inflammatory biomarkers, such as interleukinj-6 or interleukin-10 from blood and/or drainage fluid samples have been also introduced [ 14 ]. However, these markers are still far from being applied in clinical practice.…”
Section: Discussionmentioning
confidence: 99%